Global polio eradication: Where are we in Europe and what next?. Issue 36 (28th August 2018) - Celentano, Lucia Pastore; Carrillo-Santisteve, Paloma; O'Connor, Patrick; Danielsson, Niklas; Huseynov, Shahin; Derrough, Tarik; Adel Ali, Karam; Butler, Robb; Greco, Donato
Highlights: The world is very close to poliomyelitis eradication: only 37 cases confirmed in 2016. Europe is polio free from more than 20 years, but still there are consistent polio immunization gaps in clustered population groups. Immigration from polio at risk countries and high concentration of poliovirus manipulating laboratories require maintenance of a careful surveillance. National plans to respond to a poliovirus introduction are urgently needed for European countries. Poliovirus containment is still a challenge for European countries that host large amount of Sabin poliovirus containing materials. Abstract: The world was never so close to reach the polio eradication: only 37 cases notified in 2016 in only three countries, but the game is not yet at the end. The risk of polio outbreaks in the EU is smaller than it has ever been in the past, but it is not so small that we can ignore it. The EU MS must remain alert and plan and prepare for managing polio events or outbreaks because of the possible dire consequences. The IPV only vaccination schedule universally applied in EU has achieved satisfactory coverage, but constantly leaving small accumulating pockets of susceptible individuals. Moreover the IPV only schedule is not an absolute barrier against poliovirus silent transmission as demonstrated in the recent Israel outbreak. The availability of annually revised S.O.P. from WHO GPEI on the identification and response of a polio event, without local poliovirus transmission or a polio outbreak with sustained transmission, helps and challenge EU countries to update their polio national preparedness plans. The EU/EEA area, in fact, is a peculiar area regarding the polio risk both for its vaccination policy, the large polio vaccines manufactures and the constant immigration from areas at polio high risk, but also EU include cultural and financial potentials crucial to sustain the polio end game strategy and reach the benefit of a world without polio risk. Poliovirus eradication will continue to be challenged as long as there is the worldwide presence of polioviruses in laboratories and vaccine production plants. Most of the world's OPV vaccines are produced in the EU and many laboratories and research centers store and handle polio viruses. EU Member States are engaged actively in implementing the poliovirus biocontainment plans that are part of the polio eradication strategy and to certify the destruction of poliovirus strains and potentially contaminated biological materials.